The effect of caffeinated drinks on muscular endurance perfomance using circuit resistance training / Sitti Junaina Musa - Musa, Sitti Junaina (2014)
Multiple studies corroborate the ergogenic properties of caffeine for endurance performance, yet limited investigations document the effect of caffeinated drinks on muscular endurance performance using circuit resistance training (CRT). The aim of the study was to determine the effect of caffeinated drinks on muscular endurance performance using circuit resistance training (CRT) in male amateur runners. A total of 36 male amateur runners aged 20-25 years old were recruited and randomly divided into three groups (caffeinated, non-caffeinated and placebo, n= 12/groups) using stratified sampling method based on pre-treatment CRT performance results. Caffeinated group received the caffeinated drink that contain 3 mg/kg body weight dose of caffeine. Noncaffeinated and placebo group received non-caffeinated drink and plain water, respectively. The CRT, a measurement of muscular endurance was performed by all subjects following 40 minutes ingestion of drink. Total volume weight lifted (TVWL) and time of completion (TC) of CRT were recorded. Heart rate (HR) and water balance (WB) were measured before and after CRT. Body weight difference between before and after CRT was used to determine sweat rate (SR). The results show the ingestion of caffeine increased TVWL (p<0.05), TC (p<0.05) and HR (/K0.05). However, caffeine did not change SR (p>0.05) and WB (p>0.05) following ingestion. In summary, this study concludes that the acute ingestion of caffeine (3 mg/ kg) was effective to improve the muscular endurance performance.